Study of meningeal enhancement in magnetic resonance imaging in dogs with central nervous system diseases1 - Guedes, Charles H. [UNESP] (2024)
Magnetic resonance imaging (MRI) plays an important role in detecting and characterizing meningeal lesions, thus assisting in a possible ante mortem clinical diagnosis of intracranial diseases. Meningeal enhancement has been described as a sign of multiple central nervous system (CNS) disorders. The aim of this study was to evaluate meningeal enhancement on MRI of the brain of dogs and to associate them with different CNS diseases. A retrospective study of 22 dogs submitted to MRI was carried out, with a history of clinical signs of neurological diseases as an inclusion criterion for selecting these animals for the study. The data were divided according to the age and sex of the animals, and the analysis criteria were regarding the CNS diseases found, location, pattern and definition of meningeal enhancement. The results demonstrate that encephalitis and neoplasia occur more frequently among the diseases observed, with 22.7% of clinical suspicions. The site with the highest incidence was the parietal/temporal/frontal, with a 27.3% prevalence, followed by the frontal, with 18.2%. Regarding the meningeal pattern, it was found that there was 90.9% more enhancement in the pial and dural regions together than when comparing them individually. When evaluating the definition of meningeal enhancement, slight enhancement was most observed (59.1%). The present study made it possible to obtain specific information and better understand the characteristics of meningeal enhancement, including two patterns of meningeal enhancement (pial and dural) and identifying the association of values in different CNS diseases in dogs.